PENGARUH MODEL PEMBELAJARAN DISCOVERY LEARNING BERBASIS MEDIA PREZI TERHADAP HASIL BELAJAR PENDIDIKAN PANCASILA KELAS IV SEKOLAH DASAR - Ramadya Vintika Laras; Dayu RikaPerdana; Siti Nuraini; Erni (Direktorat Riset dan Pengabdian pada Masyarakat (DRPM) Universitas Bina Darma, 2025)
The problem in this research is the low learning outcomes of pancasila education for class IV students at SD Negeri 6 Metro Barat. The purpose of this research is to determine the influence of the discovery learning model based on prezi media on the learning outcomes of pancasila education of elementary school students. This research method is quasi experimental with quantitative research type and research design using non-equivalent control group design. The population of this study is 91 students and the sample is 47 students. Data collection techniques using tests in the form of pretest and posttest and non-tests in the form of observation. Data was analyzed using simple linear regression. So it can be concluded that there is a significant influence on the use of the media-based discovery learning model prezi on the learning outcomes of students in the learning of pancasila education class IV at SD Negeri 6 Metro Barat in the 2025/2026 academic year